Risk behavior amongst adolescents of a rural land development scheme in Peninsular Malaysia - Hidayah N.I.; Hanafiah ,M.S.; Idris,M.N.; Rosnah,S.; Ibrahim, N.M.S.; Nonnah, C.D (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2003)
Risk behavior amongst adolescents is an ever growing problem in Malaysia. A cross-sectional study involving 815 Form one students of secondary schools in three rural land development schemes in Peninsular Malaysia was conducted in January 2003 to determine the prevalence of risk behaviors amongst the chosen adolescents. The prevalence of low risk behavior was 51.5% and high risk behavior was 10.7%. The most prevalent risk behavior include truancy (34.4%) , loitering in public places (21.5%), bullying (14.4%), stealing (12.9%) and smoking (12.0%). Gender andparents' education level are significant predictors of risk behavior.